Estimate of the total costs of allergic rhinitis in specialized care based on real‐world data: the FERIN Study. Issue 6 (22nd January 2017) - Colás, C.; Brosa, M.; Antón, E.; Montoro, J.; Navarro, A.; Dordal, M. T.; Dávila, I.; Fernández‐Parra, B.; Ibáñez, M. D. P.; Lluch‐Bernal, M.; Matheu, V.; Rondón, C.; et al.
Abstract: Background: Despite the socioeconomic importance of allergic rhinitis (AR), very few prospective studies have been performed under conditions of clinical practice and with a sufficiently long observation period outside the clinical trial scenario. We prospectively estimated the direct and indirect costs of AR in patients attending specialized clinics in Spain. Methods: Patients were recruited at random from allergy outpatient clinics in 101 health centers throughout Spain over 12 months. We performed a multicenter, observational, prospective study under conditions of clinical practice. We analyzed direct costs from a funder perspective (healthcare costs) and from a societal perspective (healthcare and non–healthcare costs). Indirect costs (absenteeism and presenteeism [productivity lost in the workplace]) were also calculated. The cost of treating conjunctivitis was evaluated alongside that of AR. Results: The total mean cost of AR per patient‐year ( n = 498) was €2326.70 (direct, €553.80; indirect, €1772.90). Direct costs were significantly higher in women (€600.34 vs €484.46, P = 0.02). Total costs for intermittent AR were significantly lower than for persistent AR (€1484.98 vs €2655.86, P < 0.001). Total indirect costs reached €1772.90 (presenteeism, €1682.71; absenteeism, €90.19). The direct costs of AR in patients with intermittent asthma (€507.35) were lower than in patients with mild‐persistent asthma (€719.07) and moderate‐persistent asthma (€798.71) ( P = 0.006). Conclusions: The total cost of AR for society is considerable. Greater frequency of symptoms and more severe AR are associated with higher costs. Indirect costs are almost threefold direct costs, especially in presenteeism. A reduction in presenteeism would generate considerable savings for society.